Pengaruh LDR dan BOPO terhadap ROA Pada Bank Umum yang Terdaftar di BEI Tahun 2010-2020 - Nafisha Oktaviani Lutfi; Iwan Setiawan; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to examine the effect of LDR and BOPO on ROA at commercial banks listed on the IDX in 2010-2020. The types of data used in this study are time series and cross section. Sampling in this study using purposive sampling and obtained as many as 14 samples from 45 commercial banks listed on the Indonesia Stock Exchange. There are two variables used, namely Return On Assets (ROA) as the dependent variable and the financial ratio Loan to Deposit Ratio (LDR) and Operating Costs of Operating Income (BOPO) as independent variables. The method used in this study is a quantitative method. The test is done by using panel data regression which is processed using Eviews 10. The panel data method chosen is the Random Effect Model. The results showed that LDR and BOPO had a significant negative effect on ROA.